TANTANGAN DAN PELUANG DAKWAH DI ERA DIGITAL STUDI KASUS: DAKWAH UST. HANAN ATTAKI - Sunny Ghinastia Fathin; Zaafirah Nurdiana Tamathalia; Fadillah Qodri; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
This article examines the challenges and opportunities of da'wah in the digital era with the case study of Ustad Hanan Attaki. Da'wah linguistically means calling, inviting, invitation, appeal and dish. Da'wah can also be interpreted as a call or invitation. Islam was spread through da'wah. Quoted from the book Da'wah in the Koran by Yuli Umro'atin, Islam is a religion of da'wah. This religion was disseminated and introduced to mankind through missionary activities, without violence, without coercion or the use of weapons. The same thing was done by Rasulullah SAW. Quoted from the book Actual Da'wah (1998) by Didin Hafidhuddin, explaining that the aim of da'wah in general is to change the behavior of the target of da'wah so that they are willing to accept Islamic teachings and practice them in everyday life, whether related to personal, family or social issues, so that a life full of heavenly blessings and ardhi blessings, getting goodness in this world and the hereafter, and free from the punishment of hell.